"Not clinically indicated": patients' interests or resource allocation?. Issue 6874 (6th February 1993) - Hope, T; Sprigings, D; Crisp, R
Abstract : The decision that a particular intervention is not clinically indicated may conceal two quite different ethical assumptions. The first assumption is that the intervention is not of overall benefit to this patient. The second is that limited resources should not be used for this patient. These issues are discussed with reference to cardiac surgery in elderly patients with reference to the main theories of allocation: QALYs, needs theories, the sanctity of life theory, the lottery theory, and market forces.